2016
DOI: 10.1037/adb0000154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of cannabis use in an outpatient VA posttraumatic stress disorder clinic.

Abstract: Recent research has documented high rates of comorbidity between cannabis use disorders and posttraumatic stress disorder in veterans. However, despite possible links between PTSD and cannabis use, relatively little is known about cannabis use in veterans who present for PTSD treatment, particularly among samples not diagnosed with a substance use disorder. This study examined the prevalence of cannabis use and the psychological and functional correlates of cannabis use among a large sample of veterans seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 25 publications
1
26
1
Order By: Relevance
“…Male veterans reported more frequent marijuana use compared to female veterans, which fits with prior work that young adult males use marijuana more frequently than young females (Haberstick et al, 2014; Hasin et al, 2015; Johnson et al, 2015). Also, as in prior work with veterans specifically (Bonn-Miller et al, 2012; Bonn-Miller & Rousseau, 2017, Gentes et al, 2016), PTSD was associated with more problematic marijuana use. Yet protective behavioral strategies moderated the relationship between PTSD and marijuana-related consequences, such that those young veterans who screened positive for PTSD and who reported low use of protective behavioral strategies were at the most risk for consequences in the past six months.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Male veterans reported more frequent marijuana use compared to female veterans, which fits with prior work that young adult males use marijuana more frequently than young females (Haberstick et al, 2014; Hasin et al, 2015; Johnson et al, 2015). Also, as in prior work with veterans specifically (Bonn-Miller et al, 2012; Bonn-Miller & Rousseau, 2017, Gentes et al, 2016), PTSD was associated with more problematic marijuana use. Yet protective behavioral strategies moderated the relationship between PTSD and marijuana-related consequences, such that those young veterans who screened positive for PTSD and who reported low use of protective behavioral strategies were at the most risk for consequences in the past six months.…”
Section: Discussionsupporting
confidence: 65%
“…Marijuana use has been linked to increased mood, anxiety, PTSD symptoms, and psychotic disorders among VA veterans (Boden et al, 2013; Bonn-Miller et al, 2013; Galang, Babson, Boden, & Bonn-Miller, 2015; Goldman et al, 2010). Gentes and colleagues (2016) found that among veterans seeking PTSD treatment, those who used marijuana in the past six months were more likely to experience more severe PTSD, depression, and suicidality than those who did not use. Among VA patients with a cannabis use disorder in 2009, nearly three-quarters (71%) met criteria for co-occurring mental health diagnoses; more specifically, 23% also met criteria for depression and 29% also met criteria for PTSD (Bonn-Miller et al, 2012b).…”
Section: Use Of Marijuana To Cope With Mental Health Problemsmentioning
confidence: 99%
“…Indeed, no well‐controlled randomized clinical trials aimed at studying medicinal cannabis use as a treatment for PTSD have been published to date (Belendiuk et al., ). Prior research has, however, demonstrated that heavy cannabis use is associated with pulmonary problems, cognitive impairment, lower levels of educational attainment, unemployment, and increased risk for CUD and psychotic disorders (e.g., Borges et al., ; Curran et al., ; Gentes et al., ; Goldman et al., ; Hoch et al., ; Joshi et al., ; Sherman & McRae‐Clark, ). Such findings, in conjunction with the present finding that CUD was associated with increased risk for both suicidal and nonsuicidal self‐injury, lead us to caution clinicians against the use of medicinal cannabis as a first‐line treatment for PTSD or any other psychiatric condition at the present time.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have shown that veterans with posttraumatic stress disorder (PTSD), depression, and other mental health disorders are at elevated risk for both suicidal (e.g., Kimbrel, Calhoun, et al., ; Kimbrel, DeBeer et al., ) and nonsuicidal (Kimbrel, Johnson, et al., ; Kimbrel et al., ; Kimbrel, Meyer, et al., ) self‐injury. However, to our knowledge, no study has examined the relationship between CUD and self‐injury in veterans, although one recent study did find that self‐reported cannabis use was positively associated with self‐reported suicide ideation in a large sample of male veterans seeking treatment for PTSD (Gentes et al., ). This study did not, however, evaluate the relationship between cannabis use and actual self‐injury (i.e., actual suicide attempts or nonsuicidal self‐injury).…”
Section: Cannabis Use and Self‐injury In Veteransmentioning
confidence: 99%
See 1 more Smart Citation